Surely we have heard the expression many times “It doesn't matter eight eighty”.
Let's show it:
Let's call x = 80-8
Substituting x2= x (80-8) = 80x-8x remains: 80x-8x = 802-2·80·8+82
Rearranging: 808-82-8x = 802-808-80x
Factoring: 8 (80-8-x) = 80 (80-8-x)
And dividing both sides of equality by (80-8-x) we have to 8 = 80!
Where this error?
Extracted from the page //www.acertijosypasatiempos.com
The mistake is that in the last step of development It is divided by the factor (80-8-x), which is equal to 0.
This is not valid because the division between 0 does not exist.